A review of surface effects in Kapitza’s experiments on heat transfer between solids and helium II (Review Article) - Amrit, Jay (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
In a recent paper, it is shown that the thermal boundary Kapitza resistance between a solid and superfluid helium is explained by resonant scattering of phonons from surface roughness heights, as described in the Adamenko and Fuks (AF) model. We reexamine the original experiments of thermal transfer between a solid (platinum and copper) and superfluid helium conducted by P.L. Kapitza in 1940. In particular, we analyze his experimental results for the different surface treatments of the solid in light of the AF model. Time scales for diffuse scattering of phonons at the interface are estimated. Also the role of a layer of varnish on a copper surface is reinterpreted.